(untitled) (Research, Society and Development, 2021)
One of the greatest challenges in the treatment of parasitic diseases is the resistance developed by the parasites against the available drugs. Therefore, the search for therapeutic alternatives is urgent. This study carried out an integrative review of the literature that evaluated the antileishmanial, antimalarial and antitrypanosome potential of plants of the genus Casearia. The search for scientific articles was carried out on the Portal of Journals from CAPES, Biblioteca Virtual em Saúde (BVS), PUBMED and SCIELO, using the following descriptors: Casearia and antileishmania; Casearia and antimalárico; and Casearia and antitrypanosoma. A total of 122 publications were collected for screening, of which 11 were included in the integrative review. In the antileishmania activity, Casearia sylvestris stood out, with the hexane extract of the wood and stem bark and the ethanolic extract of the root bark showing activity against different species of Leishmania (IC50<100 µg/mL), but with high toxicity (CC50<100 µg/mL). Among the isolated substances, the flavonoid Tricina was shown to be active against Leishmania and non-cytotoxic. Regarding antimalarial activity, 11 extracts from 3 species, C. elliptica, C. coriaceae and C. sylvestris were shown to be active (IC50 <100 µg/mL), however, they showed high toxicity. In the antitrypanosome activity, casearins isolated from the leaves of C. sylvestris, showed great potential against the trypomastigote form of T. cruzi (IC50<3.0 µg/mL), however, they showed high toxicity. Casearia species are therefore promising in terms of their antiparasitic activity, but their toxicity is a problem. However, the flavonoids of the species have a good selectivity index and, molecular alterations and/or adequate formulations can reduce the toxicity of the other components.